Baseline Characteristics of Fabry Disease “Amenable” Migalastat Patients in Argentinian Cohort - Sebastián Jaurretche; Santiago Alonso; Mónica Calvo; Sebastián Fernandez; Heber Figueredo; Beatriz Galli; Ivanna Marin; Andrés Martinez; Silvia Mattausch; Fernando Perretta; Juan Politei; Juan Ignacio Rolon; et al. (Global Health, Epidemiology and Genomics)
Fabry disease (FD) is a multisystem lysosomal storage disorder induced by genetic variants in the alpha-galactosidase A (αGalA) gene. Some FD patients have GLA variants with a reduction in overall αGalA enzymatic activity due to mutated proteins with reduced stability, caused by protein misfolding and premature degradation, but the αGalA catalytic activity remains conserved (“amenable” genetic variants). To correct this misfolding and to prevent premature degradation, migalastat, a small iminosugar molecule was developed. We report the clinical characteristics of FD “amenable” cohort patients from Argentina, prior to starting treatment with migalastat. Seventeen Fabry adult patients were recruited from 13 Argentinian Centers; 8 males (47.1%) and 9 females (52.9%) were included. All genotypes included were missense-type “amenables” mutations. Some classic FD typical early manifestations were more frequent in patients with “classic” versus “late-onset” FD phenotype (pain, p=0.002; cornea verticillata, p=0.019). There was a statistically significant difference in estimated glomerular filtration rate in the “classic” versus “late-onset” phenotype (p=0.026) but no difference between genders (p=0.695). Left ventricular mass was similar between genders (p=0.145) and phenotypes (p=0.303). Cardiovascular risk factors were present among “late-onset” females (obesity 50% and smoke 25%). In patients who started “de novo” migalastat, the main indications were (i) heart disease, (ii) kidney damage, and (iii) pain, while in “switched from prior enzyme replacement therapy” patients, the most frequent indication was “patient decision;” this coincides with publications by other authors.